Legality of Castration in Pakistan and Legal Impediments in Legislation - Mushtaq, Mahnoor (Law and Policy Review, 2023)
Castration refers to the penalty against the rapist who has committed the cruel act of crime, for instance, rape. The prevalence of this crime in Pakistan is wearisome. The cases stated in the previous year have been alarmingly high. There are also a number of unreported cases owed to the distrust in the system with higher social pressure as well. Keeping in view the above mentioned circumstances, the government of Pakistan introduced two ordinances in the year 2020. The first ordinance deals with the gist of rape, life incarceration, and punishment of chemical castration. The second amendment deals with the procedural changes including trial of rape cases and investigation. Furthermore, the question whether this change violates the rights that are enshrined in the Constitution of Pakistan or international commitments has been discussed as well. The current study attempted to highlight the Islamic point of view pertaining to the punishment of chemical castration and legal impediment in legislation during the formation of these ordinances.